Unlocking the hepatoprotective potential of the parasitic plant Orobanche foetida Poir. aqueous extract against CCl4-induced liver injury in rat - Bedoui, Arij; Mufti, Afoua; Feriani, Anouar; Baccari, Hanene; Bouallegue, Amal; Kharrat, Mohamed; Sobeh, Mansour; Amri, Moez; Abbes, Zouhaier (Frontiers in Pharmacology, 2024)
In this current study, we explored the preventive capacity of the aqueous extract of Orobanche foetida (OF), a root holoparasite, against CCl4 prompt hepatotoxicity in rats. LC-MS/MS profiling revealed the existence of 32 compounds belonging to organic acids, benzoic acid derivatives, and hydroxycinnamic acids along with their glycosides and derivatives as well as several flavonoids. In vitro, OF demonstrated substantial antioxidant potential at DPPH and ABTS assays. Results showed that the pretreatment with OF for 6 weeks at the doses (25 mg/kg bw) and (50 mg/kg bw) countered the CCl4-induced liver injury by restoring liver injuries indicators (ALT, AST, LDH, ALP, GGT and bilirubin), normalizing lipid profile (TC, TG, LDL-C, and HDL-C), as well as, impeding DNA fragmentation. Furthermore, OF blocked the hepatic oxidative stress spurred by CCl4 administration through boosting antioxidant enzymes (GSH, CAT, and SOD) responsible of diminishing lipid peroxidation. exhibited an anti-inflammatory effect by downregulating TNF-α and IL-6 levels. OF suppressive effect on proinflammatory cytokines is further exerted by its capacity to modulate the expression of the NF-κB gene. In silico investigation revealed that among the 32 identified compounds, vanillic acid glucoside and dihydroxybenzoic acid glucoside have strong and stable bindings with the active sites of three key inflammatory proteins (PARP-1, TNF-α, IL-6), which could highlight the antioxidant and anti-inflammatory capacity of. Overall, this research provides a preliminary pharmacological support for the medicinal applications of Orobanche foetida for addressing inflammatory and hepato-pathological conditions.